Negative Polarity and Domain Broadening: Evidence from Exceptive ʔilla in Levantine Arabic - Abu Helal, Abdel-Rahman Hani (Dirasat: Human and Social Sciences, 2025)
Objectives: A standard approach to the meaning and semantic licensing of negative polarity items (NPIs) takes an NPI likeindefinite any to be a scalar expression that obligatorily activates alternatives to its contextual restriction based on the notion of Domain Widening (Kadmon and Landman 1993, Chierchia 2006). The generalization underlying this approach is that an NPI induces a domain broadening effect which is subject to exhaustification in grammar. This paper contributes further evidence to this generalization by presenting and analyzing an occurrence of exceptive ʔilla in Levantine Arabic (LA) as a strong negative polarity item (NPI) with a domain broadening effect. Methods: The paper explains an analogy between NPIs and exceptive ʔilla not only through restricted distribution in semantic licensing but also through a shared tendency to showing variation in distributional strength. Results: Based on these observations, the paper finds that NPI exceptive ʔilla requires a (multi-)dimensional exhaustification analysis that attends to both truth conditional and non-truth conditional dimensions of meaning (e.g., implicatures or presuppositions). Conclusions: This finding lends further support to an NPI theory of exceptive phrases that captures their truth conditional and distributional facts by grammatical exhaustification (See Gajewski 2011; Crnič 2018; Sauerland and Yatsushiro 2023).